Údržba v průmyslu 4.0 - Černý, Rostislav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2025)
Bakalářská práce se zaměřuje na problematiku údržby a analýzu rizik při zavádění prediktivní údržby. Teoreticky je zde popsán historický vývoj údržby, vybrané moderní metody a proces analýzy rizik. Cílem je identifikovat rizika spojená se zaváděním prediktivní údržby, posoudit jejich možné následky a navrhnout vhodná ošetření rizik. Výsledkem práce jsou doporučení, která mohou napomoci efektivnímu a bezpečnému zavádění prediktivní údržby v praxi.

The bachelor’s thesis focuses on the issue of maintenance and risk analysis in the implementation of predictive maintenance. It provides a theoretical overview of the historical development of maintenance, selected modern methods, and the process of risk analysis. The objective is to identify risks associated with the implementation of predictive maintenance, assess their potential consequences, and propose appropriate risk treatments. The outcome of the thesis is a set of recommendations that can support the effective and safe implementation of predictive maintenance in practice.
Maintenance in Industry 4.0
Keywords: Průmyslová údržba; prediktivní údržba; údržba 4.0; rizika; identifikace rizik.; Industrial maintenance; predictive maintenance; maintenance 4.0; risks; risk identification.